Pengaruh Pengungkapan Emisi Karbon Pada Kinerja Lingkungan - Septiana, Pipit Arum; Ardiana, Putu Agus (Jurnal Ilmiah Wahana Pendidikan, 2024)
Environmental performance is a company's effort to participate in environmental preservation. Environmental performance is ranked by the Ministry of Environment in the form of a rating called PROPER, which is measured using colors, ranging from the best gold, green, blue, red to the worst black, which is then announced regularly to the public through the official website of the Ministry of Environment. This study includes three control variables, namely company size, environmental management system, and sustainability committee. This study aims to determine the influence of carbon emission disclosure on environmental performance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. The number of samples used in this study is 131 manufacturing companies determined using the purposive sampling method. The results of the study indicate that carbon emission disclosure positively and significantly affects environmental performance. The good company is driven to report the emissions they produce in sustainability reports as a strategy to gain legitimacy from stakeholders.